The Effect of Company Size, Profitability, and Liquidity on the Effectiveness of Internet Financial Reporting in Manufacuturing Companies Listed on the Indonesia Stock Exchange - Nurazisah, Andi Fadhilah; Haliah; Nirwana (Formosa Journal of Applied Sciences, 2024)
This research aimed: (1) to determine the simultaneous significance that affects company size, profitability, and liquidity on the effectiveness of IFR (2) to determine the partial significance that affects company size, profitability, and liquidity on the effectiveness of IFR. The variables of this study are (1) Internet Financial Reporting (IFR) as the dependent variable (Y) which is measured using 4 items, namely content, timeliness, technology used, and user support (2) company size, profitability, and liquidity as independent variables measured by log of total assets, return on assets (ROA), and current ratio. The population of this study were 108 manufacutring companies listed on the Indonesia Stock Exchange for the period 2018-2022, while the sample was 52 companies for 5 years which were taken using the Slovin method. The data collection technique was carried out using documentation. Data analysis was carried out by descriptive statistical analysis, classical assumption test, multiple linear regression test and hypothesis testing.